Clinical analysis based on 208 patients with microtia (especially reviewed oculo-auriculo-vertebral spectrum, hearing test, CT scan) - Jin, Lei; Hao, Shaojuan; Fu, Yaoyao; Zhang, Tianyu; Wang, Zhengmin (The Turkish Journal of Pediatrics, 2010)
Microtia is a common birth defect and characteristic of abnormal auricle. It can be isolated or occur as a part of syndromes involving the first and second bronchial arch structures, such as oculo-auriculo-vertebral spectrum. We conducted a careful review of the literature regarding the clinical features of patients with microtia, but found few studies with respect to the Chinese population. In this study, we explored the clinical features of a single clinic population of 208 Chinese individuals with microtia. It showed that 15 cases (7.2%) had been afflicted with middle ear cholesteatoma, which would have brought about risky complications without an immediate removal; that 12 of 68 contralateral, normal-appearing ears had presented mild to moderate conductive or combined hearing loss (21-70 dB); that the degree of hearing loss deteriorated as the grade of microtia increased, with significant differences between grades I and III (p < 0.05); and that there was a male predominance, with the right side more likely to be affected.